2015
DOI: 10.1007/s10935-015-0390-7
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Psychosocial Adversity Within the Patient-Centered Medical Home: Expert-Created Measurable Standards

Abstract: The Patient-Centered Medical Home (PCMH) may be improved by embedding identification and response for patients’ experiences with psychosocial adversity, but how this might optimally occur in practice has not been well-specified. We sought input from an expert panel to define feasible elements that could adapt the PCMH to adequately respond to patients’ experiences with psychosocial adversity. From December 2012 through September 2013, we used a Delphi process to systematically obtain expert opinions and reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…These findings are in contrast to those of our study, which suggest that the CPM builds in enough dedicated time, follows a workflow that allows for all domains of inquiry, and has a multidisciplinary team for consultation that includes behavioral health experts. The characteristics identified in this study as contributing to acceptability also align with expert recommendations for identifying and responding to psychosocial adversity in patient-centered medical homes (Bair-Merritt et al, 2015), which include having a standardized tool to capture adversity, training providers on how to address adversity experiences, having a team member with expertise in mental health, and providing culturally responsive care. These are important factors to consider for any model of primary care practice, regardless of whether a CPM is being utilized or not.…”
Section: Discussionsupporting
confidence: 55%
“…These findings are in contrast to those of our study, which suggest that the CPM builds in enough dedicated time, follows a workflow that allows for all domains of inquiry, and has a multidisciplinary team for consultation that includes behavioral health experts. The characteristics identified in this study as contributing to acceptability also align with expert recommendations for identifying and responding to psychosocial adversity in patient-centered medical homes (Bair-Merritt et al, 2015), which include having a standardized tool to capture adversity, training providers on how to address adversity experiences, having a team member with expertise in mental health, and providing culturally responsive care. These are important factors to consider for any model of primary care practice, regardless of whether a CPM is being utilized or not.…”
Section: Discussionsupporting
confidence: 55%
“…Professional development and training in TIC holds promise for making a meaningful difference in service providers' comfort and competence when engaging in the screening process. Critical areas for training include the following: (a) the impact of trauma on children and families, including intergenerational trauma; (b) selecting, administering, scoring, and interpreting standardized screening tools that are appropriate for the age and culture of those being screened; (c) determining who should be the primary informant(s) (e.g., parent, foster parent, youth, both caregivers and youth); (d) assessing adversity in ways that do not require recounting details that may be re-traumatizing; (e) adjusting the screening process when issues of gender, race/ethnicity, culture, language, and family challenges may affect the results (e.g., a female adolescent who is reluctant to report a history of sexual abuse to a male physician); (f) explaining the purpose, use, and result of screening to families; (g) making appropriate referrals to evidence-based, trauma treatment and other services (e.g., child welfare, homeless shelters, domestic violence services) following a positive screen; (h) engaging families in the process of determining next steps (e.g., by asking families what strategies have been effective in relieving trauma symptoms); (i) ensuring that children and families feel safe before ending the screening session; and (j) using self-care practices to prevent and address secondary traumatic stress due to working with families highly impacted by trauma (Bair-Merrit, Mandal, Garg, & Cheng, 2015;Fallot & Harris, 2001;Litz, Miller, Ruef, & McTeague, 2002;SAMHSA, 2014). In addition, close collaboration with mental health professionals (e.g., training, consultation, ongoing support) has had success in improving service providers' knowledge, skills, and comfort level in working with families affected by adversity (e.g., Boris, Larrieu, Zeanah, Nagle, Steier, & McNeill, 2006).…”
Section: Insufficiently Trained Workforcementioning
confidence: 99%
“…Table 1 describes those that were included in this review, indicating the name of the main author, objective, year, country, type of publication, language, and journal. [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] The origin of the selected articles corresponds to the United States (80%), the Netherlands (10%), Colombia (5%) and Israel-USA (5%). In total, 90 authors were identified, ranging from 1-8 in the different publications.…”
Section: Resultsmentioning
confidence: 99%